2020
DOI: 10.1186/s13018-020-01679-6
|View full text |Cite
|
Sign up to set email alerts
|

PENK inhibits osteosarcoma cell migration by activating the PI3K/Akt signaling pathway

Abstract: Background: This article reports the effects of proenkephalin (PENK) on osteosarcoma (OS) cell migration. Methods: A Gene Expression Omnibus (GEO) dataset was used to identify differentially expressed genes (DEGs) in OS tumor samples and normal human osteoblasts. Tumor tissue and adjacent normal tissue were collected from 40 OS patients. MG63 cells were transfected with si-PENK. Transwell migration assays and wound healing assays were performed to compare the effect of PENK on migration. Moreover, LY294002 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The PI3K/Akt pathway is well known to be a classic signaling pathway involved in the regulation of various functions, including cell survival, proliferation, invasion, and migration 18 . The experimental results described above showed that cadherin-11 was up-regulated by inflammatory factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/Akt pathway is well known to be a classic signaling pathway involved in the regulation of various functions, including cell survival, proliferation, invasion, and migration 18 . The experimental results described above showed that cadherin-11 was up-regulated by inflammatory factors.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results confirmed that IL-1β and TNF-α could up-regulate cadherin-11 expression, the specific molecular mechanism remains unclear. The PI3K/Akt pathway has been well-established as a classic signaling pathway involved in the regulation of various functions (cell survival, proliferation, invasion, and migration) 18 . A study conducted by Alkhadar reported that nerve growth factors were triggered by the PI3K/Akt pathway in oral and salivary tumor cells and induced oral and salivary tumor cells scattering and migration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we identified several hub RNAs based on the PPI network, including HP, CRH, GCG, APOA5, and PENK. Some of these genes are involved in the development of cancer, for instance, PENK is downregulated in osteosarcoma and can activate the PI3K/Akt signaling pathway to restrain osteosarcoma cell migration ( Zhang et al, 2020 ). Notably, PENK was also downregulated in our PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…PENK is also associated with the progression of head, neck, gastrointestinal stromal tumours and pancreatic cancer. 27 SST is a cyclic peptide hormone, which affects the secretion of growth hormone, gastrointestinal motility and gastrointestinal blood flow. 28 In pancreatic cancer, SST may be a promising therapeutic site, which can get stem cells rest to inhibit colon cancer.…”
Section: Discussionmentioning
confidence: 99%